The Effectiveness of Mobile Language Learning Applications (MLLA) for Vocabulary Acquisition - Ulya, Muflikhah; Basthomi, Yazid; Febrianti, Yusnita (Lingual Journal of Language and Culture; Vol 18 No 1 (2025): Lingual: Journal of Language and CultureDO - 10.24843/LJLC.2025.v18.i01.p03, 2025)
This study reviews the effectiveness of Mobile Language Learning Applications (MLLA) in vocabulary learning and acquisition, particularly for English as a Second Language (ESL) and English as a Foreign Language (EFL) learners. By analyzing research from 2020 to 2024, the review identifies key factors influencing the success of MLLA, including interactive interfaces, usability, design, content quality, and accessibility. Moreover, game-based learning elements, multimedia environments, immediate corrective feedback, spaced repetition, and dual coding systems are highlighted in enhancing vocabulary retention and recall. The findings show that the significant benefits of MLLA, offering personalized, engaging, and flexible learning experiences that support effective vocabulary acquisition. Future studies can benefit from the design towards innovation in digital vocabulary instruction.